Siidık Abdal - an example for the Bektashism of the 15th century (Journal of Alevism-Bektashism Studies, 2012)
In this article, we will try to present and give information about Sadık Abdal’s Divan. Regarding the Bektashi legends, one of the leading names stated about the conquest of Balkans by Ottomans is Seyyid Ali Sultan (Kızıldeli). Sadık Abdal is known to be one of the disciples of Seyyid Ali Sultan in Bektashi order. We have transcripted Sadık Abdal’s Divan (poetry book) to nowadays Turksh latin alphabet. The sole copy, which was copied by Rüstem Abdal, is being used during the transcription. We assume that several questions related with Bektashi order and history will be answered and new perspectives can be created afterwards with the help of the information available in this Divan. Sadık’s Divan (poetry book) gives valuable information about status of Bektashism in 15. century, the aspect of Bektashis towards the order religions and orders, also gives some information’s about toponomical datas, onomastics and events available in legendary-religious books of Bektashism like velayetname.